2007
DOI: 10.1002/cphc.200700088
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Resolved Optical Spectroscopy with Multiple Population Dimensions: A General Method for Resolving Dynamic Heterogeneity

Abstract: The discovery of the spin echo by Hahn in 1950 [1] set the stage for the development of a multitude of "coherence" spectroscopies. The expansion, elaboration and application of coherence methods [2] continues to this day in NMR, [3] electronic, [4,5] infrared [6][7][8] and Raman [9][10][11] spectroscopy. The key feature in the original spin echo-and in all subsequent coherence spectroscopies as well-is a comparison of the evolution of a coherence over two different time periods. Herein we show that a parallel,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 28 publications
0
57
0
Order By: Relevance
“…Third, even if a biexponential decay of whatever spectroscopic quantity can be identified, this is not yet a sufficient piece of evidence to assign the relaxation to a heterogeneous mechanism. As Berg et al 35 have demonstrated in the optical regime, heterogeneous and homogeneous relaxation mechanisms can generate identical decays. The same conclusion was reached in the context of solvation dynamics in non-equilibrium 2D-IR spectroscopy; fast and slow solvation modes can be coupled, or not, and third-order spectroscopy cannot resolve this.…”
Section: Theoretical Foundationsmentioning
confidence: 83%
“…Third, even if a biexponential decay of whatever spectroscopic quantity can be identified, this is not yet a sufficient piece of evidence to assign the relaxation to a heterogeneous mechanism. As Berg et al 35 have demonstrated in the optical regime, heterogeneous and homogeneous relaxation mechanisms can generate identical decays. The same conclusion was reached in the context of solvation dynamics in non-equilibrium 2D-IR spectroscopy; fast and slow solvation modes can be coupled, or not, and third-order spectroscopy cannot resolve this.…”
Section: Theoretical Foundationsmentioning
confidence: 83%
“…47,48 Figure 5a shows the fwhm of the AuO emission band in acetonitrile as a function of time over the time range of 66−300 fs.…”
Section: ■ Resultsmentioning
confidence: 99%
“…37,38 The signal is detected in the direction, k 1 − k 2 + k 3 − k 4 + k 5 . The key advantage of this geometry is that the signal is free from a background of direct third-order signal fields when the beam diameters are small compared to their separation after the sample.…”
Section: B Laser Beam Geometriesmentioning
confidence: 99%